IgM and IgA in addition to IgG autoantibodies against FcɛRIα are frequent and associated with disease markers of chronic spontaneous urticaria. Issue 12 (18th June 2020) - Altrichter, Sabine; Zampeli, Vasiliki; Ellrich, André; Zhang, Ke; Church, Martin K; Maurer, Marcus
ABSTRACT: Background: IgG autoantibodies against the high‐affinity IgE receptor, FcɛRIα, contribute the pathogenesis of autoimmune chronic spontaneous urticaria (CSU). However, it is not known whether such patients also exhibit IgM or IgA autoantibodies against FcɛRIα. To address this question we developed an ELISA to assess serum levels of IgG, IgM, and IgA autoantibodies against FcɛRIα and investigated whether their presence is linked to clinical features of CSU including the response to autologous serum skin testing (ASST). Methods: Serum samples of 35 CSU patients (25 ASST‐positive) and 52 healthy control individuals were analyzed using a newly developed competitive ELISA for IgG, IgM, and IgA autoantibodies to FcɛRIα. Results: One in four CSU patients (8/35, 24%) had elevated serum levels of IgG‐anti‐FcɛRIα compared with (3/52, 6%) healthy controls. More than half of patients had IgM (21/35, 60%) and IgA (20/35, 57%) vs (3/52, 5%) each in healthy controls. Elevated IgM, but not IgG or IgA, autoantibodies were significantly more frequent in ASST‐positive CSU patients (18/25, 72%) compared with ASSTnegative patients (3/10, 33%, P  = .022). Also, elevated levels of IgM‐anti‐FcɛRIα, but not of IgG or IgA against FcɛRIα, were linked to low blood basophil ( r  = .414, P  = .021) and eosinophil ( r  = .623, P  < .001) counts. Conclusions: Increased serum levels of IgM‐anti‐FcɛRIα are common in patients with CSU and linked to features of autoimmune CSU. The role and relevance of autoantibodies to FcɛRIα in CSU can and should be further characterized in future studies, and our novel assay can help with this. Abstract : Beside IgG against the high‐affinity IgE receptor, patients with CSU can also have IgM and IgA directed against the receptor. IgM antibodies are associated with positive autologous serum skin tests, a feature of type IIb autoimmunity. FcɛRI cross‐linking by these autoantibodies, in skin mast cells, could lead to their degranulation, which drives the development of the clinical symptoms of CSU. Abbreviations: CSU, chronic spontaneous urticaria; FcɛRI, Fcɛ receptor I